English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Solution given is 0.

The furthest I can take it (a-(1/a))/(a+2+(1/a)) and I'm not even sure I'm headed the right direction.

2007-03-09 16:17:56 · 6 answers · asked by Wintergreen_pen 2 in Science & Mathematics Mathematics

6 answers

(1/(1+(1/a))) - (a/(a+1))

1/(1+1/a) - a/(a+1) {remove unnecessary parentheses}

a(a + 1) - 1/(a + 1) {multiply 1st term by a/a}

0

2007-03-09 16:24:47 · answer #1 · answered by Anonymous · 0 0

Lets break the things out for a better picture...

(1 + 1/a) = a/a + 1/a = (a+1)/a

So, 1 / (1 + 1/a) = a/(a+1)

From here,
1 / (1 + 1/a) - [a/(a+1)]
= [a/(a+1)] - [a/(a+1)]
= 0

=) Easy!

2007-03-10 01:40:15 · answer #2 · answered by Adrianne G. 2 · 0 0

Ok. So: 1 + 1/a = a/a + 1/a = (a+1)/a. 1/(a+1)/a = a/(a+1)

So a/(a-1) - a/(a-1) = 0. :)

2007-03-10 00:20:51 · answer #3 · answered by Bob R. 6 · 1 0

(1/(1+(1/a))) - (a/(a+1))
=a/[(a+1)/a]-(a/(a+1))
=(a/(a+1))-(a/(a+1))
=0

2007-03-10 00:22:14 · answer #4 · answered by Anonymous · 0 0

Multiply the first term by a/a, and you will have
a/ (a+1)

2007-03-10 00:24:35 · answer #5 · answered by cattbarf 7 · 0 0

(1/(1+(1/a))) - (a/(a+1))
=(1/(a+1)/a)-(a/(a+1))
=(a/a+1)-(a/a+1)
=0
thats it

2007-03-10 00:23:25 · answer #6 · answered by amrita 2 · 0 0

fedest.com, questions and answers